Calcifying Odontogenic Cyst with Extensive Areas of Dentinoid: Uncommon Case Report and Update of Main Findings - Hellen Bandeira de Pontes Santos; Everton Freitas de Morais; Deborah Gondim Lambert Moreira; Luis Ferreira de Almeida Neto; Petrus Pereira Gomes; Roseana de Almeida Freitas (Hindawi Limited, 2018)
The calcifying odontogenic cyst (COC) is a benign odontogenic cyst that occurs in the gnathic bones. This cyst is part of a spectrum of lesions characterized by odontogenic epithelium containing "ghost cells," which may undergo calcification. Areas of an eosinophilic matrix material compatible dentinoid also may present adjacent to the epithelial component. However, these areas of dentinoid commonly do not appear so abundant in COCs. In this study, we report a case of intraosseous COC with extensive areas of dentinoid and perform an update regarding the clinical, radiographical, histopathological, and differential diagnosis, treatment, and prognosis of this cystic lesion.